Protective mechanisms of exogenous melatonin on chlorophyll metabolism and photosynthesis in tomato seedlings under heat stress - An, Wangwang; Wang, Guangzheng; Dou, Jianhua; Zhang, Yonghai; Yang, Qing; He, Yongmei; Tang, Zhongqi; Yu, Jihua (Frontiers in Plant Science, 2025)
Elevated temperatures severely affect plant growth, reducing yield and quality. Melatonin (MT), a plant biomolecule, is known to enhance stress tolerance, but its role in heat resistance and underlying mechanisms require further exploration. This study investigates MT’s regulatory effects on chlorophyll metabolism and photosynthesis in tomato seedlings under high-temperature stress (40°C). Tomato seedlings treated with 100 μmol MT showed improved physiological and photosynthetic performance under heat stress. MT application increased osmolytes (proline and soluble sugar), enhanced antioxidant enzyme activities [catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX)], and reduced oxidative damage markers (H2O2, O2−, malondialdehyde, and conductivity). Photosynthetic parameters, including key enzyme activities [sedoheptulose-1,7-bisphosphatase (SBPase), ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), and NADP-dependent glyceraldehyde-3-phosphate dehydrogenase (NADP-GAPDH)], photochemical efficiency [Fv/Fm and Y(II)], and photochemical quenching (Qp), were significantly improved, restoring the OJIP curve and enhancing photosynthesis. MT also regulated chlorophyll metabolism by promoting synthesis [increasing chlorophyll a and b, 5-aminolevulinic acid (ALA), Mg-protoporphyrin (Mg Proto), and protochlorophyllide (Pchlide) levels] and upregulating synthesis genes (SlHEMA1, SlPORB, SlPORC, and SlCHLI) while inhibiting degradation genes (SlCLH1, SlCLH2, SlPAO, SlPPH, and SlRCCR). These findings demonstrate that MT enhances tomato heat tolerance by protecting chlorophyll metabolism and photosynthesis, offering a theoretical basis for improving crop resilience to heat stress.